Armenia development effectiveness brief. (Metro Manila, Philippines Asian Development Bank, 2017)
The main focus of ADBs efforts in Armenia is on strengthening the economy by building or rehabilitating infrastructure and by generating business opportunities for micro, small, and medium-sized enterprises.
Keywords: Public administration -- Armenia; Electronic books